2023
DOI: 10.3389/fimmu.2023.1081790
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endogenous glucocorticoid on response to immune checkpoint blockade in patients with advanced cancer

Abstract: BackgroundPrevious studies indicate that exogenous use of glucocorticoid (GC) affects immune checkpoint inhibitor (ICI) efficacy. However, there is a paucity of clinical data evaluating the direct impact of endogenous GC on the efficacy for cancer patients with immune checkpoint blockade.MethodsWe first compared the endogenous circulating GC levels in healthy individuals and patients with cancer. We next retrospectively reviewed patients with advanced cancer with PD-1/PD-L1 inhibitor alone or combination thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Moreover, endogenous glucocorticoids (GCs) were reported to be indispensable for PD-1 induction on NK cells ( 58 ). To our knowledge, our study is the first reporting increased PD-1 expression on lymphocytes in mucosal tissue following glucocorticoid treatment, which opens new questions especially with increasing rates of oral glucocorticoid prescriptions associated with immune check point inhibitor use in a clinical setting ( 59 , 60 ), where higher endogenous glucocorticoid levels are associated with worse response rates to immune check point blockade ( 61 ). Our findings may be of importance considering that a single trial found that almost 40% of patients under immune check point inhibitor treatment for melanoma receive GCs at least for a short term ( 60 ).…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, endogenous glucocorticoids (GCs) were reported to be indispensable for PD-1 induction on NK cells ( 58 ). To our knowledge, our study is the first reporting increased PD-1 expression on lymphocytes in mucosal tissue following glucocorticoid treatment, which opens new questions especially with increasing rates of oral glucocorticoid prescriptions associated with immune check point inhibitor use in a clinical setting ( 59 , 60 ), where higher endogenous glucocorticoid levels are associated with worse response rates to immune check point blockade ( 61 ). Our findings may be of importance considering that a single trial found that almost 40% of patients under immune check point inhibitor treatment for melanoma receive GCs at least for a short term ( 60 ).…”
Section: Discussionmentioning
confidence: 88%
“…GCs can potentiate the inhibitory effect of PD-1 by upregulating its expression on tumor-infiltrating T and NK cells. Cui et al [ 25 ] found in a study on gastric cancer that, compared with non-responsive gastric cancer patients, responsive gastric cancer patients still have lower endogenous GC levels. Nascentes et al [ 11 ] also found in a study on melanoma that the expression of genes involved in GC activation ( Hsd11b1 ) was significantly higher in ICI non-responders than in responders.…”
Section: Discussionmentioning
confidence: 99%
“…IHC staining was performed according to our previously published procedures. 10 The tumor specimens were reacted overnight at 4°C with primary mouse anti-human monoclonal CD8 and CD4 antibodies (1:200 solution; Santa Cruz Biotechnology, Santa Cruz, CA, USA) and with the PD-L1 antibody (22C3 pharmDx assay; Agilent, Carpinteria, CA, USA). After incubating with a biotin-conjugated secondary antibody for 30 min at room temperature, the sections were further treated with an avidin–biotin–peroxidase complex system (RTU VECTASTAIN Kit; Vector Laboratories, Burlingame, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For multiplex immunofluorescence staining, FFPE blocks were first heated at 65°C for 3 h according to the previous procedures. 10 The slides were then dewaxed, rehydrated, and fixed using a Leica BOND RX Auto Stainer (Leica Biosystems, YTAn00042, Buffalo Grove, IL) Subsequently, the slides were stained with six antibodies: anti-CD4 (ab133616; Abcam), anti-CD8 (MA1-80231; Thermo Fisher Scientific), anti-CD68 (MA5-12407; Thermo Fisher Scientific), anti-FoxP3 (ab215206; Abcam), anti-PD-L1 (13684S; Cell Signaling Technology), and anti-pan keratin (sc-81714; Santa Cruz Biotechnology), followed by incubation with horseradish peroxidase-conjugated secondary antibody and tyramide signal amplification. Finally, the slides were stained with 4′-6′-diamidino-2-phenylindole for 10 min at a 9:125 dilution.…”
Section: Methodsmentioning
confidence: 99%